2022
DOI: 10.1101/2022.12.27.521983
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GDF15 mediates renal cell plasticity in response to potassium depletion

Abstract: A low potassium (K+) intake is a common situation in the population of the Westernized countries where processed food is prevalent in the diet. Here, we show that expression of GDF15, a TGFbeta-related growth factor, is increased in renal tubular segments and gut parts of mice in response to low-K+ diet leading to a systemic elevation of its plasma and urine concentration. In human, under mild dietary K+ restriction, we observed that urine GDF15 excretion is correlated with plasma K+ level. Conversely to WT mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In addition to glucose metabolism and lipid metabolism described in detail below, GDF15 can affect ion metabolism and iron metabolism pathways. GDF15 can mediate proliferative effect on type A intercalated cells through the ErbB2 receptor in the presence of type 2 H,K-ATPase and maintain K+ balance [15]. Hepcidin maintains systemic iron homeostasis, and GDF15 has been shown to regulate iron metabolism by inhibiting hepcidin expression in primary hepatocytes [16].…”
Section: The Relationship Between Gdf15 and Weight Changementioning
confidence: 99%
“…In addition to glucose metabolism and lipid metabolism described in detail below, GDF15 can affect ion metabolism and iron metabolism pathways. GDF15 can mediate proliferative effect on type A intercalated cells through the ErbB2 receptor in the presence of type 2 H,K-ATPase and maintain K+ balance [15]. Hepcidin maintains systemic iron homeostasis, and GDF15 has been shown to regulate iron metabolism by inhibiting hepcidin expression in primary hepatocytes [16].…”
Section: The Relationship Between Gdf15 and Weight Changementioning
confidence: 99%
“…In the kidney, for example, Pohl et al 2 have characterized the impressive potential for context-specific remodeling that endothelial cells exhibit. In another example from the same organ system, Lasaad et al 3 have identified a major mediator of renal cell plasticity during the physiological response to reduced K+ uptake.…”
Section: Plasticitymentioning
confidence: 99%
“…Submissions of original articles are also most welcome. In the special series, these have informed on how GDF15 drives renal cell plasticity in response to potassium depletion, 8 and how increased expression of the sodiumdependent phosphate transporter NaPi-2b and paracellular phosphate permeation contribute to determining the high intestinal phosphate absorption in young animals. 9 We cordially invite you to participate in the ongoing special series with either original articles or reviews on the physiology and pathophysiology of epithelial transport.…”
Section: Kidney Membrane Proteins and Epithelial Transportmentioning
confidence: 99%